Pengaruh Supervisi Pengawas dalam Penilaian Kinerja Kepala Sekolah dan Kinerja Guru Terhadap Efektivitas Manajemen Sekolah di TK Negeri Se-Kecamatan Peusangan: Penelitian - Salma; Iskandar; Mukhlisuddin Ilyas (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the influence of supervisors' supervision on the performance of school principals, teachers' performance, and the effectiveness of school management at public kindergartens in Peusangan District. Additionally, it examines the effect of principals' and teachers' performance on the effectiveness of school management. The research applied a quantitative method with a population of 36 respondents, all of whom were included as the sample. Data were collected using a Likert-scale questionnaire and analyzed through correlation and regression techniques. The results showed that supervisors' supervision had a significant influence on principals' performance with a contribution of 36.7%, on teachers' performance by 43.8%, and on the effectiveness of school management by 41%. Furthermore, principals' performance significantly affected school management effectiveness by 13%, while teachers' performance contributed the most, at 62.7%. These findings indicate that optimizing supervision, principals' performance, and teachers' performance is essential in enhancing the effectiveness of school management at public kindergartens in Peusangan District.